Transjugular Intrahepatic Portosystemic Shunt Using the Trans-splenic Approach and a Snare Technique - Park, Juil; Kim, Hyo-Cheol (Journal of Clinical Interventional Radiology ISVIR, 2017)
Transjugular intrahepatic portosystemic shunt (TIPS) is an established procedure for the secondary prevention of variceal bleeding and management of refractory ascites. Portal vein thrombosis presents technical difficulty during TIPS due to nonvisualization of portal vein. In such patients, trans-splenic approach can be utilized to navigate thrombosed portal vein and use a snare as a fluoroscopic guidance for the intraparenchymal pass. We present the case of a 63-year old man who received the successful TIPS procedure via trans-splenic access without any complication.
Keywords: transjugular intrahepatic portosystemic shunt; trans-splenic approach; portal vein thrombosis